SISTEM PENGELOLAAN PESANTREN DALAM MEBENTUK SIKAP KEMANDIRIAN SANTRI - Rizqi Amelia; Laily Masruroh; Burhanuddin Ridlwan (Program Studi Pendidikan Agama Islam, Fakultas Agama Islam, Universitas Hasyim Asy'ari Tebuireng Jombang, Indonesia, 2020)
There are three focuses on this study, namely: 1) What is the attitude of the independence of the santri in al-Washoya Islamic boarding school, 2) What is the management system of Islamic boarding schools in al-Washoya Islamic Boarding School, and 3) What are the supporting factors and constraints on the pesantren management system independence of santri in al-Washoya Islamic boarding school. This research is included in qualitative research. This research was conducted in the Al-Washoya Ngoro Jombang Islamic boarding school, using a phenomenological qualitative approach. Data collection techniques are carried out by Observation, Interview, and Documentation. Based on the results of the study: 1) informing self-reliance on santri, the students were taught various skills such as in the field of fashion, cooking, and entrepreneurship from these activities. It was hoped that the santri would be able to live independently without relying on others. 2) the management system is centered on caregivers and is assisted by clerics and administrators, all activities that have been designed can work well, because of good cooperation between the various parties incorporated in them. And the support and motivation that makes the students enthusiastic to become better people and can live independently. 3) The supporting factors are motivation, support, and assistance from caregivers, clerics, and administrators in assisting students to implement each activity and facilities provided. The inhibiting factor is the limited time due to the many activities that exist, besides that, it is also difficult for the new santri to adapt to the environment and with the activities in the Islamic boarding school.